(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
In the new global health report, air pollution has been regarded as one of the leading causes of deadly diseases in both rural and urban area. The major causes of Air Pollution are the particulate matters (PM). Several researches have been carried out on air quality and concentration of PM in different states of Nigeria. So far, however, there has been little discussion about the annual concentration of particulate matters (PM) in Nigeria. The aim of this paper is to analyze the annual concentration of PM from January2021 – December2021 in some states in Nigeria using real-time air quality data obtained from PurpleAir.com. Results obtained from this study have shown that the annual concentration of PM2.5 in the study locations in Abuja, Kogi, Edo and Port Harcourt is greater than 20 µg/m3 which is beyond the annual Air quality standards regulation while for PM10.0, Abuja and Port Harcourt exceeded 40µg/m3 (recommended value for PM10.0) and therefore can be said to be highly polluted